Negative association between chorus cicada Amphipsalta zelandica and armillaria root disease in kiwifruit - Logan, D.P.; Alspach, P.A. (New Zealand Plant Protection, 2007)
Armillaria root disease is a serious fungal disease of kiwifruit that can ultimately end in the death of infected vines One commerciallyavailable treatment for infected vines is to inject compost teas into subsoil with compressed air Compost teas are applied to improve soil and hence plant health and their use is based on the generalisation that healthy plants have fewer pests Accordingly there is a suggestion that healthy kiwifruit vines free of armillaria root disease support fewer cicadas Exuviae of the dominant cicada species in kiwifruit Amphipsalta zelandica (Boisduval) were counted and symptoms of armillaria root disease scored for 300 contiguous vines in a commerciallymanaged block of kiwifruit More A zelandica exuviae were found on healthy vines than on vines with symptoms of armillaria root disease and in this instance the generalisation that healthy plants have fewer pests was not true